2022
DOI: 10.1038/s41562-022-01354-2
|View full text |Cite
|
Sign up to set email alerts
|

Third-party punishment by preverbal infants

Abstract: Third-party punishment of antisocial others is unique to humans and seems to be universal across cultures. However, its emergence in ontogeny remains unknown. We developed a participatory cognitive paradigm using gaze-contingency techniques, in which infants can use their gaze to affect agents displayed on a monitor. In this paradigm, fixation on an agent triggers the event of a stone crushing the agent. Throughout five experiments (total N = 120), we show that eight-month-old infants punished antisocial other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Second, a growing number of studies have shown prosocial behaviors have early developmental roots, including people displaying prosocial behaviors like fairness, trust, and reciprocity as children and even infants (Gummerum et al., 2010; Kanakogi et al., 2022; McAuliffe et al., 2015). However, it remains unclear whether prosocial behaviors in children are affected by social and nonsocial uncertainty, and whether children use strategies, like adults, to decrease/increase their prosocial behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a growing number of studies have shown prosocial behaviors have early developmental roots, including people displaying prosocial behaviors like fairness, trust, and reciprocity as children and even infants (Gummerum et al., 2010; Kanakogi et al., 2022; McAuliffe et al., 2015). However, it remains unclear whether prosocial behaviors in children are affected by social and nonsocial uncertainty, and whether children use strategies, like adults, to decrease/increase their prosocial behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Kanakogi and colleagues has demonstrated that infants recognize the social goals of aggression and protection. Specifically, infants have been shown to avoid and punish aggressive agents (Kanakogi et al, 2013, 2022), and, from 6 months of age, preferentially approach agents who intervene to prevent aggression from occurring over those who do not intervene (Kanakogi et al, 2017). Control conditions confirmed that infants' preference for protective interveners was not due to intervention making an agent appear more social: Infants did not prefer an agent who engaged in mere social approach in a non‐protective way.…”
Section: Evidence For Infants' Sensitivity To Prosocial and Antisocia...mentioning
confidence: 99%
“…Aggressive behaviors have long been understood as serving different functions, which are recognized even by infants and toddlers. For example, infants and toddlers evaluate aggressive actions that defend a victim more positively than aggressive actions that harm a victim (Geraci, 2020; Geraci & Surian, 2021; Kanakogi et al, 2022). Thus, from early in life, individuals understand and make judgments about aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Children interpret and evaluate signals from parents and do not passively accept commands from others” (Dahl, 2018; p. 237). This perspective gains empirical evidence from excellent work examining infant evaluations of aggressive actions toward third parties (Geraci, 2020; Geraci & Surian, 2021; Kanakogi et al, 2022), which recognize even infants as “thinkers” or “judges” and not just performers of aggressive behaviors. In other words, according to the interactionist perspective, children actively construct their own moral development, and are influenced by, but not merely passive recipients of, parental beliefs and commands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation